خطاب الرحلة والإسلام الأباضى خلال العصر الوسيط والفترة الحديثة - المريمي, محمد (الرحلة والغيرية, 2008)

Moufdi Zakaria (1908-1977) - Bendamèche, Abdelkader (Les grandes figures de l'art musical algérien, 2008)
Keywords: Biographies

Botanical and chemical characterization of frankincense resin from Dhofar - Ribechini, Erika; Raffaelli, Mauro; Colombini, Maria Perla (A port in Arabia between Rome and the Indian Ocean: 3rd C.BC-5th C.AD, 2008)
Keywords: Botanique -- Oman

Scientific activity in Dhofar (2000 - 2004): botanical mission of Florence University - Raffaelli, Mauro; Tardelli, Marcello; Mosti, Stefano (A port in Arabia between Rome and the Indian Ocean: 3rd C.BC-5th C.AD, 2008)
Keywords: Botanique -- Oman

تجديد الفقه وتيسيره - الشعيلي, خلفان بن سنان (أعمال ندوة تطور العلوم الفقهية - التقنين والتجديد في الفكر الإسلامي المعاصر, 2008)

المقاربة الانتربولوجية في الموسيقى التونسية والعربية، إشكالية الآليات والاهداف - قوجة, محمد (أنثروبولوجيا الموسيقى، الواقع والآفاق, 2008)

"Sadaqan agilan wa-agilan": Einige Anmerkungen zu Form und Inhalt von Ehedokumenten in Oman - Hoffmann-Ruf, Michaela (Die Grenzen der Welt: Arabica et Iranica ad honorem Heinz Gaube, 2008)

Coins of the Omani Imams during the Buyid Period: Studying the Bahla Hoard - Salimi, Abdulrahman al- (Die Grenzen der Welt: Arabica et Iranica ad honorem Heinz Gaube, 2008)
Keywords: Numismatique -- Oman

al-Baruni, Za‘ima Sulayman (1910–1976) - Ashour, Radwa; Ghazoul, Ferial; Reda-mekdashi, Hasna (Arab Women Writers: A Critical Reference Guide, 1873-1999, 2008)
Libyan literary pioneer and short-story writer born in Jadu, located in Libya’s western mountains. She is the daughter of anti-colonial fighter Sulayman al-Baruni. She received her early education in Turkish in Istanbul and then returned to Libya, where she completed her studies in the field of Arabic. She witnessed the various phases of her father’s struggle and after his death settled in Tripoli. She worked in education after Libyan independence and published her literary works in Libyan newspapers and magazines. She collected and edited critical editions on her father’s life and poetry. She participated in the Afro-Asian Women’s Conference held in Cairo in 1960.
Keywords: Biographies -- Djebel Nefousa -- 20e siècle

مناهج التجديد لدى فقهاء عمان المعاصرين وأثره في التقنين الفقهي - باجو, مصطفى بن صالح (أعمال ندوة تطور العلوم الفقهية - التقنين والتجديد في الفكر الإسلامي المعاصر, 2008)

I giuristi šafi‘iti nel sultanato di Zanzibar - Declich, Lorenzo (Religione e politica: mito, autorità, diritto, 2008)
Keywords: Fiqh; Zanzibar

Pour une anthropologie de la libération ? - Rey, Pierre-Philippe (Nouvel Organon Inaliénable et Réflexif, 2008)

Protection du patrimoine culturel et transformation socioculturelle : la "vallée du M'zab" un site classé patrimoine mondial en Algérie - Schmitt, Thomas M. (Les pays du Maghreb. Contributions de la géographie humaine allemande, 2008)
Keywords: Monuments -- conservation -- Mzab

East Africa - Hoffman, Valerie J. (The Islamic World, 2008)

Les circoncellions: Formation d'une élite rurale monastique autonome dans l'Afrique du Nord des IVe e Ve siècles - Pottier, Bruno (Revolte und Sozialstatuts von der Spaetantike bis zur fruehen Neuzeit, 2008)
Keywords: Donatisme

al-Munāẓarāt bayna ‘l-Ibāḍiyya al-Wahbiyya wa’l-Firaq al-ukhrà bi-Bilād al-Maghrib khilāla ‘l-Qarnayni al-thālith wa’l-rābiʿ/al-tāsiʿ wa’l-ʿāshir - Ḥasan, Muḥammad b. Mūsà (al-Madhāhib al-Islāmiyya bi-Bilād al-Maghrib min al-Taʿaddud ilà ‘l-Waḥda, 2008)
Based (mainly) on: Barrādī: al-Jawāhir al-Muntaqāt; Bārūnī, Sul.: al-Azhār al-Riyāḍiyya; Darjīnī: Ṭabaqāt; Masākanī, Abū Ḥafṣ ʿAmrūs b. Fatḥ: Uṣūl al-Daynūna al-Ṣafiya; Ibn al-Ṣaghīr: Akhbār al-A’imma al-Rustamiyyīn; Ibn Sallām: K. fīhi Bad’ al-Islām; Shammākhī: Siyar; Ṭālibī 1978; Warjlānī: K. al-Sīra wa-Akhbār al-A’imma; Wisyānī: Siyar al-Wisyānī.
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-

From another world! A possible Būyid origin of the decorated Miḥrāb of Central Oman? - Bandyopadhyay, Soumyen (Intercultural relations between South and Southwest Asia: studies in commemoration of E.C.L. During Caspers (1934 - 1996), 2008)
Keywords: Archéologie -- Oman

Textual sources on an Islamic African past: Arabic material in Zanzibar’s National Archive - Bang, Anne K. (The meanings of Timbuktu, 2008)
Keywords: Zanzibar

Makānat Samā’il al-Fikriyya wa’l-Adabiyya - Salīmī, Maḥmūd b. Mubārak al- (Samā’il ʿabra ‘l-Tārīkh, al-. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Samā’il Yawmay al-Ithnayn wa’l-Thulāthā’ 10 wa-11 Dhū ‘l-Qaʿda al-muwāfiq 12 wa-13 Dīsimbir 2005, 2008)
Keywords: Vie intellectuelle -- Oman

al-Maʿālim al-Athariyya li-Wilāyat Samā’il - Mudaylawī, ʿAlī b. Rāshid al- (Samā’il ʿabra ‘l-Tārīkh, al-. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Samā’il Yawmay al-Ithnayn wa’l-Thulāthā’ 10 wa-11 Dhū ‘l-Qaʿda al-muwāfiq 12 wa-13 Dīsimbir 2005, 2008)
Keywords: Archéologie -- Oman

al-ʿĀdāt wa’l-Taqālīd fī Wilāyat Samā’il - Hāshimī, Sulaymān b. Sayf al- (Samā’il ʿabra ‘l-Tārīkh, al-. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Samā’il Yawmay al-Ithnayn wa’l-Thulāthā’ 10 wa-11 Dhū ‘l-Qaʿda al-muwāfiq 12 wa-13 Dīsimbir 2005, 2008)
Keywords: Moeurs et coutumes -- Oman

Samā’il wa-Makānatuhā al-Thaqāfiyya wa’l-Ijtimāʿiyya fī ‘l-Tārīkh al-Qadīm wa’l-Muʿāṣir - Hāshimī, Mubārak b. Sayf b. Saʿīd al- (Samā’il ʿabra ‘l-Tārīkh, al-. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Samā’il Yawmay al-Ithnayn wa’l-Thulāthā’ 10 wa-11 Dhū ‘l-Qaʿda al-muwāfiq 12 wa-13 Dīsimbir 2005, 2008)

Jughrāfiyat Wilāyat Samā’il - Balūshī, ʿAlī b. Saʿīd al- (Samā’il ʿabra ‘l-Tārīkh, al-. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Samā’il Yawmay al-Ithnayn wa’l-Thulāthā’ 10 wa-11 Dhū ‘l-Qaʿda al-muwāfiq 12 wa-13 Dīsimbir 2005, 2008)
Keywords: Géographie -- Oman

Wilāyat Samā’il fī ʿAṣr al-Nahḍa - Bakrī, Khalfān b. Sulṭān al- (Samā’il ʿabra ‘l-Tārīkh, al-. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Samā’il Yawmay al-Ithnayn wa’l-Thulāthā’ 10 wa-11 Dhū ‘l-Qaʿda al-muwāfiq 12 wa-13 Dīsimbir 2005., 2008)

Qurayyāt fī ʿAṣr al-Nahḍa - Jahḍamī, Muḥammad b. Sayf (al-Qurayyāt ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī’l-Fatra min 4-5 Dhū ‘l-Ḥijja 1427 H. al-muwāfiq 25-26 Dīsimbir 2006, 2008)

Wilāyat Qurayyāt: Khaṣā’iṣ al-Mawḍiʿ wa’l-Imkāniyyāt al-Siyāḥiyya - Ḥatrūshī, Sālim b. Mubārak al- (al-Qurayyāt ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī’l-Fatra min 4-5 Dhū ‘l-Ḥijja 1427 H. al-muwāfiq 25-26 Dīsimbir 2006, 2008)

al-Mawrūthāt al-Shaʿbiyya fī Qurayyāt, al-ʿĀdāt wa’l-Taqālīd - Daramkiyya, ʿĀ’isha bint Ḥamad al- (al-Qurayyāt ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī’l-Fatra min 4-5 Dhū ‘l-Ḥijja 1427 H. al-muwāfiq 25-26 Dīsimbir 2006, 2008)

al-Ḥayāt al-Fikriyya li-Wilāyat Qurayyāt - Baṭṭāshī, Aḥmad b. Khālid (al-Qurayyāt ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī’l-Fatra min 4-5 Dhū ‘l-Ḥijja 1427 H. al-muwāfiq 25-26 Dīsimbir 2006, 2008)
Keywords: Vie intellectuelle -- Oman

al-Makāna al-Tārīkhiyya li-Wilāyat Qurayyāt - Akhzamī, Saʿīd b. Sālim al- (al-Qurayyāt ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī’l-Fatra min 4-5 Dhū ‘l-Ḥijja 1427 H. al-muwāfiq 25-26 Dīsimbir 2006, 2008)
Keywords: Oman -- Histoire

al-Shaykh Muḥammad b. Shāmis al- Baṭṭāshī Faqīhan - Siyābī, ʿAbdallāh b. Rāshid al- (Qirā’āt fī Fikr al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Iḥtifā’an bi-Dhikrà al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī 5-6 Jum. I 1428 al-muwāfiq 21-22 Māyū 2007, 2008)
Keywords: Biographies; Biographies -- Oman

al-Jawānib al-Tārīkhiyya fī Mu’allafāt al-Shaykh al-Baṭṭāshī - Kindī, al-Khaṭṭāb b. Aḥmad al- (Qirā’āt fī Fikr al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Iḥtifā’an bi-Dhikrà al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī 5-6 Jum. I 1428 al-muwāfiq 21-22 Māyū 2007, 2008)

Qirā’a fī Kitāb Salāsil al-Dhahab li’l-ʿAllāma al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī - Dardīrī, al-Ṭāhir Muḥammad al- (Qirā’āt fī Fikr al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Iḥtifā’an bi-Dhikrà al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī 5-6 Jum. I 1428 al-muwāfiq 21-22 Māyū 2007, 2008)

al-Shaykh Muḥammad b. Shāmis al- Baṭṭāshī: Ḥayātuhu wa-Aʿmāluhu - Baṭṭāshī, Ḥārith b. Muḥammad al- (Qirā’āt fī Fikr al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Iḥtifā’an bi-Dhikrà al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī 5-6 Jum. I 1428 al-muwāfiq 21-22 Māyū 2007, 2008)
Keywords: Biographies -- Oman

Faqīh al-Shuʿarā’ wa-Shāʿir al-Fuqahā’: al-Baṭṭāshī Shāʿiran - Bakkā’, Muḥammad Kāẓim al- (Qirā’āt fī Fikr al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Iḥtifā’an bi-Dhikrà al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī 5-6 Jum. I 1428 al-muwāfiq 21-22 Māyū 2007, 2008)
Keywords: Poésie -- Oman

Adawāt Kitābat al-Makhṭūṭāt fī ‘l-Bī’a al-ʿUmāniyya - Rābiḥī, Muḥammad al-; Ḥarrāṣī, Nabhān al- (Makhṭūṭāt al-ʿUmāniyya, al-: kayfa waṣalat ilaynā. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Yawm al-ithnayn 15 Jumādà ‘l-ūlà 1427 H. al-muwāfiq 12 Yūnyū 2006, 2008)
Keywords: Manuscrits -- Oman

al-Ṭuruq al-mustakhdama fī Kitābat al-Makhṭūṭ al-ʿArabī wa-Zakhrafatihi wa-Tajlīdihi - Ḥajjī, Khalfān b. Zahrān al- (Makhṭūṭāt al-ʿUmāniyya, al-: kayfa waṣalat ilaynā. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Yawm al-ithnayn 15 Jumādà ‘l-ūlà 1427 H. al-muwāfiq 12 Yūnyū 2006, 2008)
Keywords: Manuscrits -- Conservation

al-Naskh wa’l-Tadāwul - Balūshī, Ibrāhīm b. Ḥasan al- (Makhṭūṭāt al-ʿUmāniyya, al-: kayfa waṣalat ilaynā. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Yawm al-ithnayn 15 Jumādà ‘l-ūlà 1427 H. al-muwāfiq 12 Yūnyū 2006, 2008)

Āl Hāshim al-Rustāqiyyūn wa-Makānatuhum al-ʿIlmiyya - Kharūṣī, Muhannā b. Khalfān b. ʿUthmān al- (Aʿlām al-Ṭibb fī ʿUmān fī ‘l-Qarnayni al-tāsiʿ wa’l-ʿāshir al-Hijriyyayni, min. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī ‘l-Fatra min 7 wa-8 Muḥarram 1427 al-muwāfiq 6 wa-7 Fabrāyir 2006, 2008)

Lamaḥāt Manhajiyya wa-Adabiyya fī Mu’allafāt al-Aṭibbā’ Āl Hāshim: al-Ṭabīb Rāshid b. ʿUmayra Namūdhajan - Khāliṣ, Walīd Maḥmūd (Aʿlām al-Ṭibb fī ʿUmān fī ‘l-Qarnayni al-tāsiʿ wa’l-ʿāshir al-Hijriyyayni, min. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī ‘l-Fatra min 7 wa-8 Muḥarram 1427 al-muwāfiq 6 wa-7 Fabrāyir 2006, 2008)

Qirā’a fī thalāthi Qaṣā’id Ṭibbiyya Makhṭūṭa li’l-Shaykh al-Ṭabīb Rāshid b. ʿUmayra b. Thānī “al-ʿAynī” al-Rustāqī al-ʿUmānī min Āl Hāshim - ʿIbrī, Ḥusayn al- (Aʿlām al-Ṭibb fī ʿUmān fī ‘l-Qarnayni al-tāsiʿ wa’l-ʿāshir al-Hijriyyayni, min. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī ‘l-Fatra min 7 wa-8 Muḥarram 1427 al-muwāfiq 6 wa-7 Fabrāyir 2006, 2008)

al-Taṭbīqāt al-Ṭibbiyya fī Mu’allafāt Rāshid b. ʿUmayra al-Rustāqī - Hinā’ī, ʿAlī b. Ṭālib b. ʿAlī al- (Aʿlām al-Ṭibb fī ʿUmān fī ‘l-Qarnayni al-tāsiʿ wa’l-ʿāshir al-Hijriyyayni, min. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī ‘l-Fatra min 7 wa-8 Muḥarram 1427 al-muwāfiq 6 wa-7 Fabrāyir 2006, 2008)

Qirā’a fī K. Fākihat Ibn al-Sabīl li’l-Ṭabīb Rāshid b. ʿUmayra b. Thānī al-ʿAynī al-Rustāqī al-ʿUmānī - Fārisī, ʿAbd al-ʿAzīz al- (Aʿlām al-Ṭibb fī ʿUmān fī ‘l-Qarnayni al-tāsiʿ wa’l-ʿāshir al-Hijriyyayni, min. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī ‘l-Fatra min 7 wa-8 Muḥarram 1427 al-muwāfiq 6 wa-7 Fabrāyir 2006, 2008)

The Ibāḍīs - Hoffman, Valerie J. (The Islamic World, 2008)

الفقه الأباضي في مرحلة التأسيس : المدونة نموذجاً وفي عهد النهضة والتجديد : الشيخان بيوض وبكلي نموذجين - الطالبي, عمار (أعمال ندوة تطور العلوم الفقهية - التقنين والتجديد في الفكر الإسلامي المعاصر, 2008)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981); Fiqh; Réformisme -- Mzab

التآلف والتسامح بين الأديان والمذاهب جزيرة جربة أنموذجا - الصولى, علي بن محمد (أعمال ندوة التآلف والوئام بين الأديان والتحديات الثقافية الدولية الراهنة, 2008)
Keywords: Tolérance religieuse -- Djerba

The Moors and the Portuguese: Sea charts and Navigational Skills - Agius, Dionisius A. (Continuity and change in the realms of Islam: studies in honour of Professor Urbain Vermeulen, 2008)
Keywords: Navigation -- Oman

L'affaire Jean de la Goutte : religieux et laïcs dans la diplomatie jésuite en Méditerranée (1553-1555) - Fabre, Pierre-Antoine (Le commerce des captifs : les intermédiaires dans l'échange et la rachat des prisonniers en Méditerraneée, XVe-XVIIIe siècle, 2008)

The Makran-Baluch-African Network In Zanzibar And East Africa During The XIXth Century - Nicolini, Beatrice (Uncovering the History of Africans in Asia, 2008)
Keywords: Zanzibar

Retour à Ghardaïa - Amhis, Yacine (Entre deux rives. Exil et transmission, 2008)
Keywords: Judaïsme -- Mzab

D’une langue de contact entre berbères ibadites - Brugnatelli, Vermondo (Berber in contact: linguistic and sociolinguistic perspectives = Le berbère en contact: études en linguistique et sociolinguistique, 2008)
Keywords: Linguistique

Littérature religieuse à Djerba. Textes oraux et écrits - Brugnatelli, Vermondo (Oralité et nouvelles dimensions de l'oralité: intersections théoriques et comparaisons des matériaux dans les études africaines, 2008)
Keywords: Linguistique

Témoignages archéologiques sur les activités halieutiques de Meninx - Drine, Ali (Ressources et activités maritimes des peuples de l'Antiquité: actes du colloque international de Boulogne-sur-Mer, 12, 13 et 14 mai 2005, 2008)
Keywords: Archéologie -- Djerba